PEMBERIAN PENYULUHAN PENDIDIKAN SEBAGAI INVESTASI MASA DEPAN MELALUI PENGUATAN MOTIVASI BELAJAR PADA MASYARAKAT DI YAYASAN BINA INSAN MANDIRI DEPOK - Ade Irma Suryani; Nurul Huda; Dina Kusuma Astuti; Tety Winda Siregar (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Education is a form of long-term investment that requires the sacrifice of time, financial resources, as well as mental, emotional, and physical effort. In the era of globalization and technological advancement, understanding the importance of investing in education has become increasingly crucial, as it directly contributes to improving the quality of human resources and economic growth. Quality education is capable of producing competent workers who play a role in increasing productivity and national income. In addition to its economic impact, education also contributes to enhancing social welfare and the overall quality of a nation through the development of skilled and competitive individuals. As a form of commitment to sustaining education, the Community Service Team (Abdimas) of Universitas Gunadarma organized an educational outreach program for parents of students at the Bina Insan Mandiri Foundation study group located in Pancoranmas District, Depok City. This activity aims to provide in-depth understanding of the importance of education as preparation and investment for the future